Tislelizumab-induced hemophagocytic lymphohistiocytosis in a patient with microsatellite instability-high colon cancer and coexisting systemic lupus erythematosus: a case report and literature review - Jiao, Pengqing; Wang, Song; Wu, Jianhua; Zhao, Yufei; Han, Jiaxu; Sha, Ziyue (Frontiers in Oncology, 2025)
Immune checkpoint inhibitors (ICIs) have profoundly transformed the treatment landscape for microsatellite instability-high (MSI-H) colorectal cancer (CRC). However, immune-related adverse events (irAEs) remain a common and unpredictable complication among patients undergoing ICI therapy. Hemophagocytic lymphohistiocytosis (HLH), a rare and life-threatening irAE, is triggered by hyperactivated immune cells and excessive secretion of proinflammatory cytokines. We report a case of an MSI-H female patient with a history of systemic lupus erythematosus (SLE) who developed HLH after treatment with the anti-programmed cell death protein 1 (PD-1) antibody tislelizumab. After treated with tislelizumab 31 days, the patient presented with fever, pancytopenia, hemophagocytosis in bone marrow, elevated ferritin and triglyceride levels, and decreased fibrinogen. A diagnosis of HLH was confirmed with an H-score of 264. Despite steroid therapy, the patient’s HLH progressed rapidly. Etoposide was deemed intolerable, and tocilizumab and immunoglobulin were declined due to financial constraints. Regrettably, the patient succumbed to HLH within 16 days of diagnosis. This is the first reported case of ICI-induced HLH in an MSI-H colon cancer patient with a history of SLE, prompting an analysis of the potential mechanisms underlying the induction of HLH in this case. Clinicians should be vigilant for the development of HLH during ICI treatment and initiate combination therapy as early as possible upon onset of HLH.